2007
DOI: 10.1080/14622200701243144
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over effects of smoking cue exposure on working memory performance

Abstract: The present study investigated the effects of drug cue exposure on working memory performance in cigarette smokers. Adult smokers (N=23) deprived for 12 hr performed a working memory task during which they were exposed to three types of task-irrelevant stimuli: Pictures containing smoking related-content, pictures devoid of smoking content, and a fixation cross. Consistent with prior research, we found that drug cue exposure affected the processing of subsequent items (i.e., carryover effects). Specifically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Past research suggests that brain activity in response to evocative stimuli (such as emotional stimuli and cues for drugs of abuse) can "carry over" to neutral stimuli in the same scanning block, thereby progressively undermining the contrast in activation between control cues and experimental cues (Childress et al, 2008;Goldman et al, 2013;Sharma & Money, 2010;Waters, Sayette, Franken, & Schwartz, 2005;Wilson, Sayette, Fiez, & Brough, 2007). We anticipated that these "carry-over" effects would impact our ability to detect differences, but there is no metric for when this would take place during the scan.…”
Section: Imagingmentioning
confidence: 98%
“…Past research suggests that brain activity in response to evocative stimuli (such as emotional stimuli and cues for drugs of abuse) can "carry over" to neutral stimuli in the same scanning block, thereby progressively undermining the contrast in activation between control cues and experimental cues (Childress et al, 2008;Goldman et al, 2013;Sharma & Money, 2010;Waters, Sayette, Franken, & Schwartz, 2005;Wilson, Sayette, Fiez, & Brough, 2007). We anticipated that these "carry-over" effects would impact our ability to detect differences, but there is no metric for when this would take place during the scan.…”
Section: Imagingmentioning
confidence: 98%
“…But there also are plenty of instances in which contrasts of interest were not significant (e.g., studies in which heavy and light smokers do not show differential increases in craving following smoking cue exposure), which could have been affected by order interactions that were not corrected by counterbalancing. For instance, Wilson et al (2007) failed to observe an effect of smoking cues on a working memory task but found that this null finding was in large part a function of carryover effects. Moreover, it is unknown how many studies failing to detect significant differences went unpublished, and as noted above, some studies failing to link cue reactivity effects to subsequent relapse may have been affected by a noisy manipulation of cues due to carryover effects.…”
Section: Does It Matter?mentioning
confidence: 99%
“…Performance during the neutral cue was disrupted if subjects had just previously been exposed to the smoking cues (compared with when the control cue exposure came first). As noted by Wilson et al (2007), "performance on a wide variety of cognitive tasks is likely to exhibit similar [carryover] effects." (p. 617).…”
Section: Evidence For Carryover Effectsmentioning
confidence: 99%
See 2 more Smart Citations